If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(6) + -3x = 9 Multiply 3 * 6 18 + -3x = 9 Solving 18 + -3x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -3x = 9 + -18 Combine like terms: 18 + -18 = 0 0 + -3x = 9 + -18 -3x = 9 + -18 Combine like terms: 9 + -18 = -9 -3x = -9 Divide each side by '-3'. x = 3 Simplifying x = 3
| 2p^2-7pq+6q^2=0 | | 3(2z-5)=5(z+4) | | 3m^2+11mn+6n^2=0 | | 0.45(60)+0.6x=0.5(60+x) | | 3x-5(x-3)=-9+2x-8 | | 4y^2=20y | | 0.45(60)+0.6x=0.55(60+x) | | 7-12s-4s^2=0 | | 8x-12=2x^2 | | x^2-15x-2=0 | | 1-5b-8b^2=0 | | 4x^2+y^2-8x+4y+4=0 | | X(x-3)=x+3 | | 9+6k-8k^2=0 | | 5+7x-6x^2=0 | | 2x^2+7x+14=0 | | 6a^2-5a-2=0 | | 2x^2+7+14=0 | | 6a^2-51-2=0 | | r^2-8r=0 | | 4y^2-y-3=0 | | (2x^3*-7)(6x^3-6)=0 | | 8m^3n^4-22m^5n^6= | | -7x^2-66x-27=0 | | (x-5)(x+1)=4 | | 2+5*x=4x | | 3r^2-2r-5=0 | | -6y-5=7+9y | | 3r^2-24-5=0 | | 10r+8=58 | | 72m^7n+24n= | | 49m^5n^3+28mn^4= |